2016
DOI: 10.1002/asi.23768
|View full text |Cite
|
Sign up to set email alerts
|

Book genre and author gender: Romance>Paranormal‐Romance to Autobiography>Memoir

Abstract: Although gender differences are known to exist in the publishing industry and in reader preferences, there is little public systematic data about them. This article uses evidence from the book‐based social website Goodreads to provide a large scale analysis of 50 major English book genres based on author genders. The results show gender differences in authorship in almost all categories and gender differences the level of interest in, and ratings of, books in a minority of categories. Perhaps surprisingly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…The same is true for some other words and linguistic features, such as exclamation marks (Burger, Henderson, Kim, & Zarrella, 2011;Volkova & Yarowsky, 2014). More generally, there are gender differences in the extent to which sentiment is expressed in the social web (Bagić Babac & Podobnik, 2016;Rangel & Rosso, 2016;Thelwall, Wilkinson, & Uppal, 2010;Volkova & Yoram, 2015), perhaps echoing common stylistic differences (e.g., Koppel, Argamon, & Shimoni, 2002;Thelwall, 2016). It is not clear whether the differences are at the sentiment level or the linguistic levels, however, because the differences could be stylistic or substantive.…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for some other words and linguistic features, such as exclamation marks (Burger, Henderson, Kim, & Zarrella, 2011;Volkova & Yarowsky, 2014). More generally, there are gender differences in the extent to which sentiment is expressed in the social web (Bagić Babac & Podobnik, 2016;Rangel & Rosso, 2016;Thelwall, Wilkinson, & Uppal, 2010;Volkova & Yoram, 2015), perhaps echoing common stylistic differences (e.g., Koppel, Argamon, & Shimoni, 2002;Thelwall, 2016). It is not clear whether the differences are at the sentiment level or the linguistic levels, however, because the differences could be stylistic or substantive.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of 64 English language books that were nominated for book awards (2007–2011) found that although winning books attracted more readers, their Goodreads ratings decreased because they received more attention and criticism from book readers (Kovács & Sharkey, ). There is little correlation between book‐based metrics (book reviews and ratings) and social activities (numbers of friends and followers) (Thelwall & Kousha, ). An analysis of a sample of 8,538 history and geography books found a low but statistically significant positive Spearman correlation (.212) between the number of Goodreads ratings and the number of Scopus citations.…”
Section: Introductionmentioning
confidence: 99%
“…age, gender, genre, price, company type, etc. (Crozier 1999;Shehu et al 2014;Thelwall 2017). At the interface of scientific activities and literary fiction production, we expect scientific authorship of literary fiction to be dependent on similar influences.…”
Section: Modeling Scientific Authorship Of Literary Fictionmentioning
confidence: 99%